Defective Ru nanocluster-oxygen coordinated Ru monatomic double-active-site porous nanosheet electrocatalyst for hydrogen hydroxide precipitation and preparation method of defect Ru nanocluster-oxygen coordinated Ru monatomic double-active-site porous nanosheet electrocatalyst

The defect Ru nano cluster-oxygen-oxygen-oxygen-oxygenic dual-active porous nanosioprocatalabial catalyst prepared by low-temperature self-assembly-carbonization-pickling-pickled method-wetting-wetting-wetting-wetting-wetting-wetting-wetting-wetting-wetting-wetting-wetting-wetting-wetting-wetting-wetting-wetting-wetting-wetting-wetting-in-situ RU single atom The lack of sexual dual -function HOR/HER electrocatalysts significantly improve the electrocatalyst activity of hydroxide reactions and hydrogen output reactions.

CN119368169APending Publication Date: 2025-01-28LANZHOU UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410752879.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-12
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

No efficient alkaline dual-function HOR/HER electrocatalyst has been found in the prior art, which is difficult to meet the demand for hydrogen hydroxide precipitation.

Method used

Prepare the defective RU single-atomic porous nanocrone electrocatalyst by low temperature self-assembly-carbonization-pickled-pickling-wetting-wetting-wetting-wetting-wetting-wetting-wetting-wetting-wetting-wetting-wetting-wetting-wetting-wetting-wetting-wetting-wetting-wetting-wetting-watering method of RU Nano-clustered-Overnoteable

Benefits of technology

The high decentralization and adjacent to the RU nano -cluster and oxygen setting are achieved, which improves the surface area and pore rate of the electrocatalyst, and significantly improves the electrocatalytic activity of hydroxide reactions and hydrogen response.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119368169A_ABST
    Figure CN119368169A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of fuel cells and water electrolysis, in particular to a defect Ru nanocluster-oxygen coordinated Ru monatomic double-active-site porous nanosheet electrocatalyst for hydrogen hydroxide precipitation and a preparation method of the defect Ru nanocluster-oxygen coordinated Ru monatomic double-active-site porous nanosheet electrocatalyst. And preparing the defect Ru nanocluster-oxygen coordinated Ru monatomic double-active-site porous nanosheet electrocatalyst. The invention has the following advantages: in the defective Ru nanocluster-oxygen coordinated Ru monatomic double-active site porous nanosheet electrocatalyst prepared by low-temperature self-assembly, carbonization, acid pickling, wet impregnation and in-situ reduction, the defective Ru nanoclusters and oxygen coordinated Ru monatomic double-active sites are highly dispersed and adjacent to each other; in addition, the electrocatalyst has a large specific surface area and high porosity, and utilization of active sites is facilitated. The electrocatalyst has very high electrocatalytic activity, and is suitable for a hydroxide reaction of a hydroxyl exchange membrane fuel cell anode and a hydrogen evolution reaction of an electrolyzed water cathode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fuel cells and water electrolysis, and in particular to a defective Ru nanocluster-oxygen coordinated Ru single atom double active site porous nanosheet electrocatalyst for hydrogen hydroxide precipitation and a preparation method thereof. Background Art

[0002] With the consideration and concern about the global fossil energy crisis, and pollutants (SO x 、NO x , fine particulate matter) and greenhouse gas content increase, there is an urgent need to explore clean and sustainable energy resources and gradually reduce the use of fossil energy. Hydrogen energy has always been considered the cleanest and most promising energy source due to its high quality energy density and carbon-free nature. Clean hydrogen fuel can be obtained by collecting renewable energy (such as solar energy, wind energy, geothermal energy and tidal energy) to decompose water. This hydrogen can be further stored and used in ammonia production, oil refining, coke / iron production, fuel cells, electric vehicles and residential life. However, unlike energy sources such as oil and natural gas that already exist on the earth, hydrogen energy does not exist naturally, so it needs to be produced or converted from other resources before it can be used.

[0003] Hydrogen obtained from steam methane reforming and coal gasification accounts for more than 95% of the global hydrogen fuel production. Obviously, this process consumes a lot of fossil fuels, causing environmental pollution and carbon dioxide emissions. In contrast, water splitting to produce hydrogen uses water as the only raw material, so it is considered a green and sustainable method. Secondly, fuel cells are a device that directly converts chemical energy into electrical energy, with the advantages of high energy conversion efficiency, low operating temperature, fast startup and high energy density.

[0004] The hydrogen oxidation reaction (HOR) in fuel cells and the hydrogen evolution reaction (HER) in water electrolyzers are two key reactions in the hydrogen cycle. An ideal alkaline bifunctional HOR / HER electrocatalyst should have the following characteristics: (1) Multiple active sites are coupled to one electrocatalyst to adsorb multiple intermediates and avoid adsorption-desorption competition between reactant species. (2) Different active sites should be adjacent and uniformly dispersed in the support, with synergistic interactions to regulate their d-band centers. (3) The active components should have ultrasmall sizes, and the support should be able to provide convenient mass transfer channels to maximize atomic utilization efficiency. However, no such HOR / HER bifunctional and efficient electrocatalyst has been reported. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a defective Ru nanocluster-oxygen coordinated Ru single atom dual-active site porous nanosheet electrocatalyst for hydrogen hydroxide evolution and a preparation method thereof to solve the problems existing in the background technology.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A method for preparing a defective Ru nanocluster-oxygen coordinated Ru single atom dual-active site porous nanosheet electrocatalyst for hydrogen hydroxide precipitation, characterized in that it comprises the following steps:

[0008] Step 1: Preparation of metal organic framework nanosheets

[0009] (1) N,N-dimethylformamide, ethanol and deionized water were mixed in a 250 mL round-bottom flask to form a homogeneous solution A;

[0010] (2) dissolving terephthalic acid and zinc chloride in the solution A obtained in (1) in sequence, and subjecting the solution to ultrasonic treatment to obtain a solution B;

[0011] (3) injecting triethylamine into solution B and stirring at 15-30° C. for 8 hours to form solution C;

[0012] (4) filtering solution C, washing the filtrate with ethanol and drying it at 60° C. to obtain metal organic framework nanosheets;

[0013] Step 2: Preparation of defective Ru nanoclusters-oxygen-coordinated Ru single atom dual-active site porous nanosheet electrocatalyst

[0014] (1) placing the metal organic framework nanosheet prepared in step 1 (4) in a tube furnace, carbonizing it at 950° C. for 3 hours under an inert atmosphere, and cooling it to room temperature;

[0015] (2) The product after heat treatment in (1) was immersed in 0.5 mol L -1 HNO 3 and magnetically stirred at room temperature for 12 h to remove possible Zn residues;

[0016] (3) washing the sample obtained by acid washing in (2) with deionized water until the filtrate is neutral, and drying at 60° C. overnight to obtain porous oxygen-doped carbon nanosheets;

[0017] (4) The porous oxygen-doped carbon nanosheets were dispersed in deionized water, ultrasonically treated, and Ru metal salt was added, and magnetic stirring was performed for 12 hours to allow the Ru metal cations to coordinate well with the oxygen in the carbon nanosheet carrier; then, the Ru-adsorbed carbon nanosheet carrier sample was collected by continuous vacuum filtration, deionized water washing, and drying at 60°C overnight;

[0018] (5) The Ru-adsorbed carbon nanosheet carrier sample is annealed in an inert atmosphere at a temperature of 600 to 900° C., and then cooled to obtain a defective Ru nanocluster-oxygen-coordinated Ru single-atom porous nanosheet electrocatalyst.

[0019] Preferably, in step 1 (1), the concentration of N,N-dimethylformamide in the deionized water / ethanol mixed solution is 2 to 12 mL mL -1 .

[0020] Preferably, in step 1 (2), the concentration of terephthalic acid in the deionized water / ethanol mixed solution is 20 to 40 mg mL -1 The concentration of zinc chloride in the deionized water / ethanol mixed solution is 20-50 mg mL -1 .

[0021] Preferably, in step 1 (3), the concentration of triethylamine in the deionized water / ethanol mixed solution is 0.1 to 0.5 mL mL -1 .

[0022] Preferably, in step 2 (4), the concentration of the porous oxygen-doped carbon nanosheets in deionized water is 1 to 30 mg mL -1 The concentration of the Ru metal salt in deionized water is 1 to 10 mg mL -1 .

[0023] Preferably, in step 2 (4), the Ru metal salt is one or more of ruthenium chloride, ruthenium carbonyl, ruthenium nitrate, and ruthenium acetylacetonate.

[0024] Preferably, in step 1 (2) and step 2 (4), the ultrasonic treatment time is 0.1 to 1 hour.

[0025] Preferably, in step 2 (1) and step 2 (5), the inert atmosphere is one or a mixture of two or more of helium, argon and nitrogen.

[0026] The second aspect of the present invention provides a defective Ru nanocluster-oxygen coordinated Ru single atom dual-active site porous nanosheet electrocatalyst.

[0027] The third aspect of the present invention provides the use of defective Ru nanocluster-oxygen coordinated Ru single atom dual-active site porous nanosheet electrocatalyst in the hydrogen oxidation reaction of the anode of the hydroxide exchange membrane fuel cell and the hydrogen evolution reaction of the cathode of the electrolytic water.

[0028] Compared with the prior art, the present invention has the following advantages: the defective Ru nanoclusters and the oxygen-coordinated Ru single atom dual active sites in the defective Ru nanocluster-oxygen-coordinated Ru single atom dual active sites porous nanosheet electrocatalyst prepared by low-temperature self-assembly-carbonization-acid washing-wet impregnation-in-situ reduction are highly dispersed and adjacent to each other, and the electrocatalyst has a large specific surface area and a high porosity, which is conducive to the utilization of active sites. The electrocatalyst of the present invention has a very high electrocatalytic activity and is suitable for the hydrogen oxidation reaction of the anode of the hydroxide exchange membrane fuel cell and the hydrogen evolution reaction of the cathode of the electrolytic water. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 is a scanning electron microscope image (SEM) of the metal organic framework nanosheet in Example 1 of the present invention;

[0030] Figure 2 is a scanning electron microscope image of the defective Ru nanocluster-oxygen coordinated Ru single atom dual active site porous nanosheet structure electrocatalyst in Example 1 of the present invention;

[0031] Figure 3 is the N of the defective Ru nanocluster-oxygen coordinated Ru single atom dual active site porous nanosheet structure electrocatalyst in Example 1 of the present invention. 2 Adsorption-desorption curves;

[0032] Figure 4 This is a spherical aberration corrected scanning transmission electron microscopy image (AC-HAADF-STEM) of the defective Ru nanocluster-oxygen coordinated Ru single atom dual active site porous nanosheet structure electrocatalyst in Example 1 of the present invention;

[0033] Figure 5 is a pore size distribution diagram of the defective Ru nanocluster-oxygen coordinated Ru single atom dual active site porous nanosheet structure electrocatalyst in Example 1 of the present invention;

[0034] Figure 6 is the alkaline hydrogen oxidation curve of the defective Ru nanocluster-oxygen coordinated Ru single atom dual active site porous nanosheet structure electrocatalyst and the commercial platinum / carbon electrocatalyst in Example 1 of the present invention;

[0035] Figure 7 The mass activity and price activity diagram of the defective Ru nanocluster-oxygen coordinated Ru single atom dual-active site porous nanosheet structure electrocatalyst and the commercial platinum / carbon electrocatalyst in alkaline hydrogen oxidation in Example 1 of the present invention;

[0036] Figure 8 is the alkaline hydrogen evolution curve of the defective Ru nanocluster-oxygen coordinated Ru single atom dual active site porous nanosheet structure electrocatalyst and the commercial platinum / carbon electrocatalyst in Example 1 of the present invention;

[0037] Fig. 9 It is a mass activity and price activity diagram of the defective Ru nanocluster-oxygen coordinated Ru single atom dual active site porous nanosheet structure electrocatalyst and commercial platinum / carbon electrocatalyst in alkaline hydrogen evolution in Example 1 of the present invention. DETAILED DESCRIPTION

[0038] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] The platinum / carbon (20 wt %, TANAKA TKK) in the following examples was purchased from a commercial source.

[0040] Embodiment 1:

[0041] (1) Preparation of metal organic framework nanosheets

[0042] N,N-dimethylformamide (64 mL), ethanol (4 mL) and deionized water (4 mL) were mixed in a 250 mL round container to form a homogeneous solution A. Then, terephthalic acid (0.25 g) and zinc chloride (0.21 g) were dissolved in the above solution A in sequence and ultrasonically treated for 30 minutes to obtain solution B. Next, triethylamine (1.6 mL) was injected and stirred at 25 ° C for 8 hours to form solution C. Finally, solution C was filtered, and the product metal organic framework nanosheets were rinsed with ethanol and dried at 60 ° C;

[0043] (2) Preparation of defective Ru nanoclusters-oxygen-coordinated Ru single atom dual-active site porous nanosheet electrocatalysts

[0044] The prepared metal organic framework nanosheets were placed in a tube furnace and carbonized for 3 hours at 950°C in an argon atmosphere. After cooling to room temperature, the heat-treated product was immersed in 0.5 mol L -1 HNO 3, and magnetically stirred at room temperature for 12 hours to remove possible Zn residues. The acid-washed sample was washed with deionized water until the filtrate was neutral and dried at 60°C overnight to obtain porous oxygen-doped carbon nanosheets. Afterwards, 100 mg of porous oxygen-doped carbon nanosheets were dispersed in 10 mL of deionized water, ultrasonically treated for 30 minutes, and 25 mg of ruthenium acetylacetonate was added and magnetically stirred for 12 hours to allow Ru metal cations to coordinate well with oxygen in the carbon nanosheet support. The carbon nanosheet support sample adsorbed with Ru was collected by continuous vacuum filtration, deionized water washing and drying at 60°C overnight. Finally, the above powder was annealed in an argon atmosphere at 700°C, and the product was cooled to obtain a Ru single-atom porous nanosheet electrocatalyst with defective Ru nanoclusters coordinated with oxygen.

[0045] like Figure 1 As shown, the SEM results show that the product obtained in step (1) is Zn-MOF ultrathin nanosheets;

[0046] like Figure 2 As shown, the SEM results show that the product obtained in step (2) not only retains the ultra-thin nanosheet morphology of Zn-MOF, but also has a porous support structure after carbonization and acid washing, and is further loaded with ruthenium, such as Figure 3 As shown, the specific surface area is 1772m 2 g -1 ;

[0047] like Figure 4 As shown, the AC-HAADF-STEM results show that the product obtained in step (2) is a structure in which single atoms and clusters coexist, and the clusters have obvious structural defects;

[0048] like Figure 5 As shown, the pore size distribution diagram shows that the product obtained in step (2) has a mesoporous structure;

[0049] like Figure 6 As shown, the prepared defective Ru nanoclusters-oxygen coordinated Ru single atoms dual-active-site porous nanosheet structure electrocatalyst has better alkaline HOR activity than commercial Pt / C;

[0050] like Figure 7 As shown, the prepared defective Ru nanoclusters-oxygen-coordinated Ru single atoms with dual-active-site porous nanosheet structure electrocatalyst has better mass activity and price activity than commercial Pt / C in alkaline HOR;

[0051] like Figure 8 As shown, the prepared defective Ru nanoclusters-oxygen coordinated Ru single atoms dual-active site porous nanosheet structure electrocatalyst has better alkaline HER activity than commercial Pt / C;

[0052] like Fig. 9As shown, the prepared defective Ru nanoclusters-oxygen-coordinated Ru single atoms dual-active-site porous nanosheet structure electrocatalyst has better mass activity and price activity than commercial Pt / C in alkaline HER.

[0053] Embodiment 2:

[0054] (1) Preparation of metal organic framework nanosheets

[0055] N,N-dimethylformamide (32 mL), ethanol (4 mL) and deionized water (4 mL) were mixed in a 250 mL round container to form a homogeneous solution A. Then, terephthalic acid (0.20 g) and zinc chloride (0.30 g) were dissolved in the above solution A in sequence and ultrasonically treated for 30 minutes to obtain solution B. Next, triethylamine (1.6 mL) was injected and stirred at 25 ° C for 8 hours to form solution C. Finally, solution C was filtered, and the product metal organic framework nanosheets were rinsed with ethanol and dried at 60 ° C;

[0056] (2) Preparation of defective Ru nanoclusters-oxygen-coordinated Ru single atom dual-active site porous nanosheet electrocatalysts

[0057] The prepared metal organic framework nanosheets were placed in a tube furnace and carbonized for 3 hours at 950°C in an argon atmosphere. After cooling to room temperature, the heat-treated product was immersed in 0.5 mol L -1 HNO 3 , and magnetically stirred at room temperature for 12 hours to remove possible Zn residues. The acid-washed sample was washed with deionized water until the filtrate was neutral and dried at 60°C overnight to obtain porous oxygen-doped carbon nanosheets. Afterwards, 100 mg of porous oxygen-doped carbon nanosheets were dispersed in 10 mL of deionized water, ultrasonically treated for 30 minutes, and 25 mg of ruthenium acetylacetonate was added and magnetically stirred for 12 hours to allow Ru metal cations to coordinate well with oxygen in the carbon nanosheet support. The carbon nanosheet support sample adsorbed with Ru was collected by continuous vacuum filtration, deionized water washing and drying at 60°C overnight. Finally, the above powder was annealed in an argon atmosphere at 700°C, and the product was cooled to obtain a Ru single-atom porous nanosheet electrocatalyst with defective Ru nanoclusters coordinated with oxygen.

[0058] Embodiment three:

[0059] (1) Preparation of metal organic framework nanosheets

[0060] N,N-dimethylformamide (64 mL), ethanol (4 mL) and deionized water (4 mL) were mixed in a 250 mL round container to form a homogeneous solution A. Then, terephthalic acid (0.25 g) and zinc chloride (0.21 g) were dissolved in the above solution A in sequence and ultrasonically treated for 30 minutes to obtain solution B. Next, triethylamine (3.2 mL) was injected and stirred at 20 ° C for 8 hours to form solution C. Finally, solution C was filtered, and the product metal organic framework nanosheets were rinsed with ethanol and dried at 60 ° C;

[0061] (2) Preparation of defective Ru nanoclusters-oxygen-coordinated Ru single atom dual-active site porous nanosheet electrocatalysts

[0062] The prepared metal organic framework nanosheets were placed in a tube furnace and carbonized for 3 hours at 950°C in an argon atmosphere. After cooling to room temperature, the heat-treated product was immersed in 0.5 mol L -1 HNO 3 , and magnetically stirred at room temperature for 12 hours to remove possible Zn residues. The acid-washed sample was washed with deionized water until the filtrate was neutral and dried at 60°C overnight to obtain porous oxygen-doped carbon nanosheets. Afterwards, 100 mg of porous oxygen-doped carbon nanosheets were dispersed in 10 mL of deionized water, ultrasonically treated for 30 minutes, and 40 mg of ruthenium acetylacetonate was added and magnetically stirred for 12 hours to allow Ru metal cations to coordinate well with oxygen in the carbon nanosheet support. The carbon nanosheet support sample adsorbed with Ru was collected by continuous vacuum filtration, deionized water washing and drying at 60°C overnight. Finally, the above powder was annealed in an argon atmosphere at 800°C, and the product was cooled to obtain a Ru single-atom porous nanosheet electrocatalyst with defective Ru nanoclusters coordinated with oxygen.

[0063] Embodiment 4:

[0064] (1) Preparation of metal organic framework nanosheets

[0065] N,N-dimethylformamide (64 mL), ethanol (4 mL) and deionized water (4 mL) were mixed in a 250 mL round container to form a homogeneous solution A. Then, terephthalic acid (0.25 g) and zinc chloride (0.21 g) were dissolved in the above solution A in sequence and ultrasonically treated for 20 minutes to obtain solution B. Next, triethylamine (1.6 mL) was injected and stirred at 25 ° C for 8 hours to form solution C. Finally, solution C was filtered, and the product metal organic framework nanosheets were rinsed with ethanol and dried at 60 ° C;

[0066] (2) Preparation of defective Ru nanoclusters-oxygen-coordinated Ru single atom dual-active site porous nanosheet electrocatalysts

[0067] The prepared metal organic framework nanosheets were placed in a tube furnace and carbonized for 3 hours at 950°C in an argon atmosphere. After cooling to room temperature, the heat-treated product was immersed in 0.5 mol L -1 HNO 3 and magnetically stirred at room temperature for 12 hours to remove possible Zn residues. The acid-washed sample was washed with deionized water until the filtrate was neutral and dried at 60°C overnight to obtain porous oxygen-doped carbon nanosheets. Afterwards, 200 mg of porous oxygen-doped carbon nanosheets were dispersed in 10 mL of deionized water, ultrasonically treated for 40 minutes, and 25 mg of carbonyl ruthenium was added and magnetically stirred for 12 hours to allow Ru metal cations to coordinate well with oxygen in the carbon nanosheet support. The carbon nanosheet support sample adsorbed with Ru was collected by continuous vacuum filtration, deionized water washing and drying at 60°C overnight. Finally, the above powder was annealed in an argon atmosphere at 600°C, and the product was cooled to obtain a Ru single-atom porous nanosheet electrocatalyst with defective Ru nanoclusters coordinated with oxygen.

[0068] Embodiment five:

[0069] (1) Preparation of metal organic framework nanosheets

[0070] N,N-dimethylformamide (64 mL), ethanol (4 mL) and deionized water (4 mL) were mixed in a 250 mL round container to form a homogeneous solution A. Then, terephthalic acid (0.25 g) and zinc chloride (0.21 g) were dissolved in the above solution A in sequence and ultrasonically treated for 30 minutes to obtain solution B. Next, triethylamine (1.6 mL) was injected and stirred at 25 ° C for 8 hours to form solution C. Finally, solution C was filtered, and the product metal organic framework nanosheets were rinsed with ethanol and dried at 60 ° C;

[0071] (2) Preparation of defective Ru nanoclusters-oxygen-coordinated Ru single atom dual-active site porous nanosheet electrocatalysts

[0072] The prepared metal organic framework nanosheets were placed in a tube furnace and carbonized for 3 hours at 950°C in a nitrogen atmosphere. After cooling to room temperature, the heat-treated product was immersed in 0.5 mol L -1 HNO 3, and magnetically stirred at room temperature for 12 hours to remove possible Zn residues. The acid-washed sample was washed with deionized water until the filtrate was neutral and dried at 60°C overnight to obtain porous oxygen-doped carbon nanosheets. Afterwards, 100 mg of porous oxygen-doped carbon nanosheets were dispersed in 10 mL of deionized water, ultrasonically treated for 30 minutes, and 25 mg of ruthenium chloride was added and magnetically stirred for 12 hours to allow Ru metal cations to coordinate well with oxygen in the carbon nanosheet support. The Ru-adsorbed carbon nanosheet support sample was collected by continuous vacuum filtration, deionized water washing and drying at 60°C overnight. Finally, the above powder was annealed in a nitrogen atmosphere at 700°C, and the product was cooled to obtain a Ru single-atom porous nanosheet electrocatalyst with defective Ru nanoclusters coordinated with oxygen.

[0073] The embodiments of the present application are described above in conjunction with the accompanying drawings, but the present application is not limited to the above-mentioned specific implementation methods. The above-mentioned specific implementation methods are merely illustrative and not restrictive. Under the guidance of the present application, ordinary technicians in this field can also make many forms without departing from the purpose of the present application and the scope of protection of the claims, all of which are within the protection of the present application.

Claims

1. A method for preparing a defective Ru nanocluster-oxygen coordinated Ru single atom dual-active site porous nanosheet electrocatalyst for hydrogen hydroxide evolution, characterized in that: The steps include: Step 1: Preparation of metal organic framework nanosheets (1) N,N-dimethylformamide, ethanol and deionized water were mixed in a 250 mL round-bottom flask to form a homogeneous solution A; (2) dissolving terephthalic acid and zinc chloride in the solution A obtained in (1) in sequence, and subjecting the solution to ultrasonic treatment to obtain a solution B; (3) injecting triethylamine into solution B and stirring at 15-30° C. for 8 hours to form solution C; (4) filtering solution C, washing the filtrate with ethanol and drying it at 60° C. to obtain metal organic framework nanosheets; Step 2: Preparation of defective Ru nanoclusters-oxygen-coordinated Ru single atom dual-active site porous nanosheet electrocatalyst (1) placing the metal organic framework nanosheet prepared in step 1 (4) in a tube furnace, carbonizing it at 950° C. for 3 hours under an inert atmosphere, and cooling it to room temperature; (2) The product after heat treatment in (1) was immersed in 0.5 mol L -1 HNO3 and magnetically stirred at room temperature for 12 h to remove possible Zn residues; (3) washing the sample obtained by acid washing in (2) with deionized water until the filtrate is neutral, and drying at 60° C. overnight to obtain porous oxygen-doped carbon nanosheets; (4) The porous oxygen-doped carbon nanosheets were dispersed in deionized water, ultrasonically treated, and Ru metal salt was added, and magnetic stirring was performed for 12 hours to allow the Ru metal cations to coordinate well with the oxygen in the carbon nanosheet carrier; then, the Ru-adsorbed carbon nanosheet carrier sample was collected by continuous vacuum filtration, deionized water washing, and drying at 60°C overnight; (5) The Ru-adsorbed carbon nanosheet carrier sample is annealed in an inert atmosphere at a temperature of 600 to 900° C., and then cooled to obtain a defective Ru nanocluster-oxygen-coordinated Ru single-atom porous nanosheet electrocatalyst.

2. The method for preparing a defective Ru nanocluster-oxygen coordinated Ru single atom dual-active site porous nanosheet electrocatalyst for hydrogen hydroxide evolution according to claim 1, characterized in that: In step 1 (1), the concentration of N,N-dimethylformamide in the deionized water / ethanol mixed solution is 2 to 12 mL mL -1 .

3. The method for preparing a defective Ru nanocluster-oxygen coordinated Ru single atom dual-active site porous nanosheet electrocatalyst for hydrogen hydroxide evolution according to claim 1, characterized in that: In step 1 (2), the concentration of terephthalic acid in the deionized water / ethanol mixed solution is 20 to 40 mg mL -1 The concentration of zinc chloride in the deionized water / ethanol mixed solution is 20-50 mg mL -1 .

4. The method for preparing a defective Ru nanocluster-oxygen coordinated Ru single atom dual-active site porous nanosheet electrocatalyst for hydrogen hydroxide evolution according to claim 1, characterized in that: In step 1 (3), the concentration of triethylamine in the deionized water / ethanol mixed solution is 0.1-0.5 mL mL -1 .

5. The method for preparing a defective Ru nanocluster-oxygen coordinated Ru single atom dual-active site porous nanosheet electrocatalyst for hydrogen hydroxide evolution according to claim 1, characterized in that: In step 2 (4), the concentration of the porous oxygen-doped carbon nanosheets in deionized water is 1 to 30 mg mL -1 The concentration of the Ru metal salt in deionized water is 1 to 10 mg mL -1 .

6. The method for preparing a defective Ru nanocluster-oxygen coordinated Ru single atom dual-active site porous nanosheet electrocatalyst for hydrogen hydroxide evolution according to claim 1, characterized in that: In step 2 (4), the Ru metal salt is one or more of ruthenium chloride, ruthenium carbonyl, ruthenium nitrate, and ruthenium acetylacetonate.

7. The method for preparing a defective Ru nanocluster-oxygen coordinated Ru single atom dual-active site porous nanosheet electrocatalyst for hydrogen hydroxide evolution according to claim 1, characterized in that: In step 1 (2) and step 2 (4), the ultrasonic treatment time is 0.1 to 1 hour.

8. The method for preparing a defective Ru nanocluster-oxygen coordinated Ru single atom dual-active site porous nanosheet electrocatalyst for hydrogen hydroxide evolution according to claim 1, characterized in that: In step 2 (1) and step 2 (5), the inert atmosphere is one or a mixture of two or more of helium, argon and nitrogen.

9. A defective Ru nanocluster-oxygen coordinated Ru single atom dual-active site porous nanosheet electrocatalyst prepared by any preparation method of claims 1 to 8.

10. The defective Ru nanocluster-oxygen coordinated Ru single atom dual-active site porous nanosheet electrocatalyst according to claim 9 is used for hydrogen oxidation reaction at the anode of a hydroxide exchange membrane fuel cell and hydrogen evolution reaction at the cathode of water electrolysis.